Pupillometry in Infancy Research. Issue 3 (26th May 2016) - Hepach, Robert; Westermann, Gert
Abstract : The human pupil is a small opening in each eye that dilates in response not only to changes in luminance, but also to novel events. Therefore, changes in pupil diameter are an attractive measure in studies on infants' and young children's physical and social cognition. However, designing and interpreting pupillometry studies for developmental populations come with caveats. Here we give an overview of how psychologically induced changes in pupil diameter have been investigated and interpreted in developmental studies. We highlight the methodological challenges when designing experiments for infants and young children and provide several suggestions to address common problems. The fact that pupillometry provides a sensitive measure of the time course of responses to novelty extends the scope of possibilities for researchers studying infant cognition and development.